2019
DOI: 10.5539/ibr.v12n5p34
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Bank Credit on Inflation in Jordan by Using Vector Auto Regression Model: A Case Study of Jordan during 1968-2017

Abstract: Previous studied revealed mixed results regarding the Banks have an influence on the inflation rate. This study aims at investigating the impact of the bank credit on the inflation rate in Jordan during the period 1968-2017 by using Vector Auto Regression Model (VAR) on the annual data. Necessary tests were conducted for this model such as Unit Root Test, Granger Causality Test, Variance Decomposition and Response Function analysis. The results reveal that there is a mutual effect between the bank credit and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Nonrestricted SVAR models have been found to have better predictive power than restricted ones (Sumarminingsih, Suharsono, Ruchjana, & Stiawan, 2019). Additionally, research using VAR has been conducted to investigate the explanatory power of bank credit on inflation rates in Jordan, and it was concluded that there is a positive effect of bank credit on the inflation rate (Al-Oshaibat & Banikhalid, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Nonrestricted SVAR models have been found to have better predictive power than restricted ones (Sumarminingsih, Suharsono, Ruchjana, & Stiawan, 2019). Additionally, research using VAR has been conducted to investigate the explanatory power of bank credit on inflation rates in Jordan, and it was concluded that there is a positive effect of bank credit on the inflation rate (Al-Oshaibat & Banikhalid, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%